Reduction of Downtime of the Durvilla Die Casting MAchine at ENKEI (M) Sdn. Bhd. MACI production Plant Line A, Using total Productive Maintenance (TPM) and Condition-based Maintenance (CBM) Approach - Bassey, Nelson David (2017)
Downtime is one of the major hazards confronting the manufacturing industry today. It accounts for majority of the loss and waste incurred in production. When unplanned breakdown or unexpected failure happens due to equipment failure, whole production line stops and production automatically stops. Therefore it would be expensive to bring the production system running condition under emergency situation (Kotwal, Dhami & Singh, 2015). Hence industries have a growing interest in new methods for maintenance and health condition assessment of machinery. Two of such methods, which this project explored, are Total Productive Maintenance (TPM) and Condition-Based Maintenance (CBM). Enkei (M) Sdn.Bhd.is a multinational company headquartered in Hanamatsu City, Shizuoka Pref. Japan. It is a subsidiary of the Enkei Corporation estabilished on 5 October 1990. The company is one of the world’s largest high quality Aluminum Wheels manufacturers. Its products include aluminium wheel for automobile & motorcycle, and various aluminium casting parts. Enkei custom wheel deliver the latest in wheel designs, composite alloy technology such as, casting forged process, rigid testing that must pass stringent JGTC Standards and unsurpassed manufacturing facilities. Despite the lean manufacturing practices adopted by Enkei and its rigorous Kaizen operation one, of the greatest wastes in its manufacturing plant is down time. Table 1 shows Down Time Ratio (DTR) of one of its plants (MACI). Hence, the focus of this project is to reduce downtime by 20% for the casting section of the MAC I plant. Conducting a pilot study on the Line A Durville Die casting machine. And to do this, the two methods (TPM & CBM) were studied: key strengths were drawn from each of them and combined into a new framework of methodology developed to solve this problem.